The response regulator SypE controls biofilm formation and colonization through phosphorylation of the syp-encoded regulator SypA in Vibrio fischeri - Morris, Andrew R. (2012)
Bacteria utilize multiple regulatory systems to modulate gene expression in response to environmental changes, including two-component signaling systems and partner-switching networks. We recently identified a novel regulatory protein SypE that combines features of both signaling systems. SypE contains a central response regulator receiver domain flanked by putative kinase and phosphatase effector domains with similarity to partner-switching proteins. SypE was previously shown to exert dual control over biofilm formation through the opposing activities of its terminal effector domains. Here, we demonstrate that SypE controls biofilms in Vibrio fischeri by regulating the activity of SypA, a STAS (sulphate transporter and anti-sigma antagonist) domain protein. Using biochemical and genetic approaches, we determined that SypE both phosphorylates and dephosphorylates SypA, and that phosphorylation inhibits SypA’s activity. Furthermore, we found that biofilm formation and symbiotic colonization required active, unphosphorylated SypA, and thus SypA phosphorylation corresponded with a loss of biofilms and impaired host colonization. Finally, expression of a non-phosphorylatable mutant of SypA suppressed both the biofilm and symbiosis defects of a constitutively inhibitory SypE mutant strain. This study demonstrates that regulation of SypA activity by SypE is a critical mechanism by which V. fischeri controls biofilm development and symbiotic colonization.